Marketing Communication Strategy in the Instagram Account @BJN.Foodies as a Culinary Promotion Media in Bojonegoro City - Zahra, Yanuba Arifatuz; Nurhaqiqi, Hanna (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Abstract: This study aims to analyze the marketing communication strategy used by the Instagram account @bjn.foodies as a culinary promotion medium in the city of Bojonegoro. The research method used is descriptive qualitative with the approach of The Circular Model of SoMe. Data were collected through interviews, observations, and documentation. The results show that @bjn.foodies successfully utilizes various Instagram features such as Reels, Stories, and Hashtags to increase visibility and interaction with the audience. The implemented marketing communications strategies include creating engaging content, optimizing posting times, and managing interactions and feedback from the audience. Additionally, interactive activities such as Q&A and giveaways help increase follower engagement and loyalty. Through this strategy, @bjn.foodies not only successfully promotes local culinary but also supports the development of SMEs in Bojonegoro